IMPLIKASI KEBIJAKAN PEMERINTAH TERHADAP SUBSIDI KENDARAAN LISTRIK DALAM LINGKUP INVESTASI - Alif Ardiansyah; Reyka Widia Nugraha; Bhim Prakoso (Bajang Institute, 2023)
International trade is a complex process involving bilateral agreements, subsidies, and balancing acts. The General Agreement on Tariffs and Trade (GATT) and the Agreement on Subsidies and Countervailing Measures (SCM) provide more detailed information regarding subsidies and incentives for exporting goods. The SCM agreement includes subsidies for export goods, such as imports and exports, and for local production towards the country's economic development. Tax holidays are also provided to encourage investment, with subsidies ranging from 50 to 100 percent. The Indonesian government has also introduced a tax holiday for electric vehicles, with a subsidy of IDR 7 million per unit. The 2020-2024 RPJMN (National Medium Term Development Plan) aims to increase science and technology capabilities and innovation in the research process and also encourage economic development for the nation, with a focus on strategic products such as lithium-ion batteries and fast charging systems. These new tax measures aim to boost international trade and local economies by providing financial support to local producers. However, the application of these tax measures may not be uniform across all countries, as some countries may have different tax rates and regulations.